Tinjauan Yuridis Tentang Perlindungan Hukum Terhadap Korban Dan Pelaku Kejahatan Berdasarkan Asas Equality Before The Law - Muh Kemal Kurniawan; Arifai Arifai; Gamlan Dagani (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Victims of crime have not received adequate protection from the state, both in physical and economic aspects, including in fulfilling other needs related to their role as witnesses in the criminal justice process. This research aims to analyze the position of crime victims in the criminal justice system in Indonesia, as well as to examine the forms of legal protection for victims and perpetrators of crime based on the principle of equality before the law. The results of the research show that the position of victims in the criminal justice system is still not receiving proportional attention and tends to be neglected, especially in the Criminal Procedure Code and Criminal Code. Nevertheless, some laws and regulations have begun to accommodate the protection of victims, although not yet optimally. In the perspective of the principle of equality before the law, legal protection for victims and perpetrators of crime should be placed equally as legal subjects who have the right to be protected by the legal system, although its implementation is not yet fully ideal.